Bleeding events with dabigatran or warfarin in patients with venous thromboembolism - Majeed, Ammar; Feuring, Martin (Thrombosis and haemostasis, 2016)
Dabigatran was as effective as warfarin for the acute treatment of venous thromboembolism in the RE-COVER and RE-COVER II trials. We compared the incidence of bleeding with dabigatran versus warfarin in pooled data from these studies. The localisation, bleeding severity, and the impact of key factors on the incidence of bleeding, were compared between the dabigatran and warfarin treatment group. Altogether, 2553 patients received dabigatran and 2554 warfarin, each for a mean of 164 days. The incidence of any bleeding event was significantly lower with dabigatran (hazard ratio [HR] 0.70; 95 % confidence interval [CI], 0.61-0.79), as was the incidence of the composite of MBEs and clinically relevant non-major bleeding events (HR 0.62; 95 % CI, 0.50-0.76). The incidence of major bleeding events (MBEs) was also significantly lower with dabigatran in the double-dummy phase (HR, 0.60; 95 % CI, 0.36-0.99) but not statistically different between the two treatment arms when the entire treatment period is considered (HR 0.73 95 % CI, 0.48-1.11). Increasing age, reduced renal function, Asian ethnicity, and concomitant antiplatelet therapy were associated with higher bleeding rates in both treatment groups. The reduction in bleeding with dabigatran compared to warfarin was consistent among the subgroups and with a similar pattern for intracranial, and urogenital major bleeding. In conclusion, treatment of venous thromboembolism with dabigatran is associated with a lower risk of bleeding compared to warfarin. This reduction did not differ with respect to the location of bleeding or among predefined subgroups.